A Study of Stress Level among Adolescents in Government and Public Schools of Delhi - Bhatia, Ranjana; Vij, Sandhya; Madhura, Deepti (JOURNAL OF INDIAN EDUCATION, 2013)
Stress has been observed as the major cause of problem for all of us. This problem has also been observed in adolescents as a result of which, behavioural problems have been on an increase amongst them. The stress also affects adolescents in terms of their academic performance as it is a major cause of anxiety within this age group. The cause of stress can be attributed to the type of school, conditions at home, peer pressure and the mental state. In the following study it has been found that the major reasons for increase in stress level and subsequent increase in anxiety are examinations, leisure time activities, home environment vis-à-vis school environment, sleep pattern and even consumption of junk food. Gender also plays a significant role in the increased/decreased level of anxiety. A significant role can be played by the teachers to reduce the stress level in adolescents. Compassion, understanding, love, care and a strong bond between the teacher and the taught can play an important role in reducing the stress level among the adolescents.